E-commerce consumer transaction: implementation of a 'trustmark' system in Malaysia / Nur Adila Omar, Siti Zubaidah Jemadi and Wan Nurul Hanini Wan Ahmad Shukry - Omar, Nur Adila; Jemadi, Siti Zubaidah; Wan Ahmad Shukry, Wan Nurul Hanini (2011)
Building consumer confidence is one of the important issues to promote electronic commerce and online shopping. RM 1.8 billion has been spent by Malaysian on online business in 2010 and 7 out of 10 Malaysian agreed if the level of security in online shopping is higher, the number will increase as such implementation of a Trustmark scheme in Malaysia would boost the confidence level of the online consumers. This research thus analyses the implementation of a Trustmark system in Malaysia. For comparative purpose, it analyses the implementation of this system in other countries such as United Kingdom, Austria and Singapore. This research also scrutinizes the loopholes in the laws that relates to online business transactions such as Electronic Commerce Act 2006, Consumer Protection Act 1999, Contracts Act 1950, Registration of Business Act 1956 and Sale of Goods Act 1957. This paper proposes the implementation of the Trustmark scheme by creating a commission in Malaysia to better safeguard and increase the level of security to regards online shopping websites in order to gain consumer confidence apart from the laws.